x+2/2=3-x+5/3

Simple and best practice solution for x+2/2=3-x+5/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+2/2=3-x+5/3 equation:



x+2/2=3-x+5/3
We move all terms to the left:
x+2/2-(3-x+5/3)=0
We add all the numbers together, and all the variables
x-(-1x+5/3+3)+2/2=0
We add all the numbers together, and all the variables
x-(-1x+5/3+3)+1=0
We get rid of parentheses
x+1x-3+1-5/3=0
We multiply all the terms by the denominator
x*3+1x*3-5-3*3+1*3=0
We add all the numbers together, and all the variables
x*3+1x*3-11=0
Wy multiply elements
3x+3x-11=0
We add all the numbers together, and all the variables
6x-11=0
We move all terms containing x to the left, all other terms to the right
6x=11
x=11/6
x=1+5/6

See similar equations:

| -8(d+1)-d-9=-9(d+4)+19 | | 7n=-189 | | 4x-90=180 | | 3x+2x-2+2x+7x+7=19 | | 5/9k-2/9=-3+3/5k | | x2=64/169 | | x-5x=750 | | x=10+0.28/1.28 | | 1/3(-12k+39)=3+11k | | y=1.28(10+0.28/1.28)-7.77 | | 7a-(4a-8a+3)+2a=10a | | 4a=34-6 | | 1.28x-7.77=-3.53+8.84 | | (x)+(x+10)+(x+50)=180 | | 2d+3.2=8.8 | | 2(2x)2+1=-3 | | 1=3y−2 | | x+3(x)+6(x)=180 | | y=3(2-4) | | 3x+6-12=4x+4 | | 5n-5=n10 | | 10+14=5y-10 | | 1/5x+1/3=-2 | | 6b=20+2b | | 5+4(x+8)=37-6(3x+11) | | 4(x-3)=-2(6-2x | | 2c+4.4=8.6 | | 54y-17=13.8 | | y=3(14-4) | | 5x-6=4x+4. | | 3x+7+4x=9 | | $3.00=0.55b |

Equations solver categories